Hubungan Kepuasan Kerja dengan Motivasi Perawat di Rumah Sakit Swasta Bandung - Tanti Lestari Mulyaningtyas; Tina Shinta Parulian; Ferdinan Sihombing (STIKes Santa Elisabeth Medan, 2021)
Background: Job satisfaction and motivation are needed by nurses in providing quality services. Rotation without considering the competencies possessed and the training that must be followed by nurses affects job satisfaction and motivation of nurses so that it becomes a problem in nursing services. Job satisfaction is an individual's attitude towards his job. Motivation is a process that describes the strength, direction, and persistence of a person in an effort to achieve goals.Methods: This study aims to determine the relationship between job satisfaction and motivation of nurses. This study uses quantitative methods, descriptive correlation design, cross sectional approach with simple random sampling technique to 222 respondents. Collecting data using a questionnaire.Results: The results of the univariate analysis were obtained, more than half of the respondents (64.9%) stated high job satisfaction and most (85.1%) had moderate motivation. Bivariate analysis using Spearmank rank results in job satisfaction having a strong relationship with motivation.Conclusion: The direction of the relationship between job satisfaction and motivation is positive, which means that if job satisfaction is high, motivation is also high. Hospitals in carrying out nurse rotation must comply with procedures and needs and consider the competence of nurses.